2018
DOI: 10.1002/jhet.3413
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antitumor Effect of Sophoridine Derivatives Bearing an Acyclic Aryloxy Phosphoramidate Mustard Functionality

Abstract: To elevate the potency of sophoridine, phosphoramidate mustard motif was incorporated to D‐ring opened sophoridine scaffold. A series of acyclic aryloxy phosphoramidate mustard functionalized sophoridine derivatives were synthesized and screened for cytostatic activity in a range of different tumor cell lines (S180, H22, K562, MCF‐7, SMMC‐7721, and LoVo). All these compounds were shown to be more sensitive to S180 and H22 cells with IC50 values ranging from 2.10 to 7.21 μM. In addition, all targeted derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Considering these issues, method A (Scheme 3) was developed to synthesize the requisite hybrids 7 via compounds 6, which were prepared through substitution of compounds 3 with phenols 4. [10] Production of 6, however, was slow and accompanied by the production of undesired disubstituted side-products. In addition, the polarities of compounds 3, 4 and 6 were similar, complicating product isolation and purification.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Considering these issues, method A (Scheme 3) was developed to synthesize the requisite hybrids 7 via compounds 6, which were prepared through substitution of compounds 3 with phenols 4. [10] Production of 6, however, was slow and accompanied by the production of undesired disubstituted side-products. In addition, the polarities of compounds 3, 4 and 6 were similar, complicating product isolation and purification.…”
Section: Chemistrymentioning
confidence: 99%
“…[9] Acrolein is a non-targeted by-product related to cyclophosphamide, which causes haemorrhagic cystitis. [10] Artemisinin has significant antimalarial activity, [11] and its derivatives have been found to have some anticancer activity in recent years. [12] Tsogoeva group and Wei group found that hybridization of DHA with active fragments could significantly enhance its anticancer activity in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,3 However, the reported compounds exhibited interesting effects in humans. 2 For example, phosphoramidates are known anticancer agents, 2,4,5,6 and antiviral products 7 effective against hepatitis B or C viruses. 8,9,10 Roles as covalent intermediates in phosphoryl group transfer reactions have also been reported during the study of the behavior of several hydrolases.…”
Section: Introductionmentioning
confidence: 99%
“…1 Introduction ophoridine (SR), an alkaloid extracted from many traditional Chinese medicine including Sophora alopecuroides L. with high content was reported to be a variety of pharmacological activities, such as anti-tumor, anti arrhythmia. [1][2][3][4] Selectively induce apoptotic cell death in a range of human cancer cells in vitro and in vivo was also proved for SR. Results showed that SR exhibited anti-cancer activity on glioma cells by inducing cell apoptosis, inducing ROS accumulation, and activating mitochondrial signal pathways.…”
mentioning
confidence: 99%